Anti‐inflammatory and cytotoxic activities of constituents from Wedelia trilobata (L.) Hitchc. Issue 1 (25th February 2019) - Thao, Nguyen Phuong; Binh, Pham Thanh; Luyen, Nguyen Thi; Cong, Nguyen Duy; Dang, Nguyen Hai; Dat, Nguyen Tien
Abstract: Using various chromatographic separations, five compounds (1 –5 ) were isolated from a methanol extract of W. trilobata leaves. Their structures were elucidated to be paniculoside‐IV (1 ), 3‐ O ‐[ β ‐D‐glucopyranosyl(1‐4)‐ β ‐D‐glucoronopyranosyl] oleanolic acid 28‐ O ‐ β ‐D‐glucopyranosyl ester (2 ), 5, 7, 4'‐trihydroxyflavone (3 ), apigenin 7‐ O ‐ β ‐D‐glucopyranoside (4 ), and 3, 4‐dihydroxy‐cinnamic acid (5 ), by detailed analysis via spectroscopic techniques (IR, 1D, 2D NMR and ESI‐MS data) as well as comparison with those reported. This is the first report of2 from Wedelia genus. Furthermore, the effects of the isolated compounds on LPS‐induced NO production in RAW264.7 cells and cytotoxic activity (against A549, MCF‐7, Hep3B, and PC3 cell lines) were also evaluated.